PENGARUH KEBERADAAN MAKAM KIAI MUZAKIR TERHADAP KESADARAN LINGKUNGAN MASYARAKAT PESISIR DESA BEDONO, KECAMATAN SAYUNG, DEMAK - Wati, Diah Ismoyo (P2KK LIPI, 2013)
Environmental problem is a global problem that must be looked for the best solution, immediately. During these remedies, this solution from the technical side, ignore the socio-cultural conditions, but still lefting many problems. The cases in Bedono, environmental problems can be solved through the magical event with the presence of the shrine Kiai Muzakir. This tomb was able to give effect to the environmental awareness Bedono villagers, Sayung, Demak. The existence of the shrine that shows the ecological wisdom. Development of environmental management based on a critical assessment of ecological wisdom has the advantage would be more appropriate to the cultural and ecological conditions of the environment. Keywords: problem, environment, effect, tomb, Kiai Muzakir, Bedono.